SISTEM INFORMASI E-COMMERCE PADA TOKO KOSMETIK SIGER BEAUTY DI BANDAR LAMPUNG - Wenti Prisilia Novita; Irwan Adi Pribadi; Anie Rose Irawati (Jurnal Pepadun, 2021)
E-Commerce is a dynamic collection of technology, applications and business process that connect companies and consumers and certain communities where goods between sellers and consumers of various commodities on a large scale isexchange through electronic systems, such as radio, television, and computer networks or the internet. Such thing can be accepted as e-commerce if it has 9 components, namely consumers, sellers, products, infrastructure, front-end, back-end, intermediaries, partners, and support services.  The e-commerce information system at Siger Beauty Store has been developed by providing features that have criteria as e-commerce. These features consist of registering customers, selecting products, ordering products,and paying. Meanwhile, for internal company, it provides feature to maintain product data, promo data, order data, and transaction report data of the products.